Excepcionais: um estudo sobre a relação professora-aluno - Lima, Celia Ribeiro da Costa (1989)
This dissertation examines the relationship between the teacher and the mentally retarded student. Based on Gregory Bateson’s theory of communication, a phenomenological-based qualitative investigation wasperformed for the purpose of estabilishing the behavior and communication was performed for the purpose of estailishing the behavior and communication between teacher and student in the natural surroundings where they occur: the classroom. Eleven teachers and thity-two students, in three schoolsfor exceptional children, underwent observation. The presupposition that this be an infantilistic relationship, that makes it difficult for the student to perceive himself, was our starting point. Initially, the subject was placed within larger themes, which are education and the nature of the exceptional child. It was observed that authoritarianism and a tendency towards behavioral uniformity – the consequence of disregarding the difference – become more harmful when imposed on the exceptional child. They prevent the individual’s recognition of his deficiency and evolution by becoming conscious of his limitations. The student becomes infantilistic and prevented from grouwing up as an autonomous person.